A case-control study of two polymorphisms of HIF1A in children with cleft lip/palate and in their mother - Yıldırım, İbrahim; Koçak, Nadir; Kamaşak, Kağan (Journal of Surgery and Medicine, 2020)
Aim: Palatogenesis is a metabolic event that occurs in the initial stages of fetal life. Reports indicate that hypoxia is a critical condition in the formation and elevation of the palate and fusion of the lips. It is known that both environmental and genetic factors play important roles in hypoxia. The ability of the cells to respond to changes in the oxygen pressure that lead to hypoxia depends on the activation of a transcription factor family known as hypoxia-inducible factors (HIFs). This study was conducted to determine the distribution of two polymorphisms of hypoxia-inducible factor 1, alpha subunit (HIF1A) in children with cleft lip/palate and their mothers. Methods: Two polymorphic structures of HIF1A (Pro582Ser and Ala588Thr) were studied in children with cleft lip/palate and their mothers along with control group children and mothers using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. DNA fragments were monitored by agarose gel electrophoresis after cleavage. Results: In Ala588Thr comparison, no difference was observed between mothers, children, and their controls. Regarding Pro582Ser, there were differences in the comparison of maternal and children genotypes with control groups (P=0.034 and P=0.023, respectively). In allelic comparisons, there was a difference between mothers of children with cleft lip/palates and the control group (P=0.001). Although this was different in children, it was not as high as in mothers (P=0.026). Conclusion: HIF1A polymorphisms that change the proline residues may affect the activity or lifespan of HIF1A protein and play a role in the formation of cleft lip/palate.